Dask the definitive guide - Rocklin, Matthew; Powers, Matthew; Pelgrim, Richard (O'Reilly Media, Inc., 2023)
The exponentially-increasing volume and complexity of data make scalability and reliability increasingly challenging issues. But while modern systems contain multi-core CPUs and GPUs that have the potential for parallel computing, many Python tools weren't designed to leverage this parallelism. Using Dask to parallelize Python workflows delivers a competitive advantage by reducing turn-around time, freeing you to work on more interesting or complex data problems.
"Early release, raw & unedited."
Keywords: Python (Computer program language); Data mining; Electronic data processing -- Distributed processing; Information visualization; Electronic data processing; Distributed processing